Walking Exercise Simultaneously Combined With Neuromuscular Electrical Stimulation of Antagonists Resistance Improved Muscle Strength, Physical Function, and Knee Pain in Symptomatic Knee Osteoarthritis: A Single-Arm Study - Matsuse, Hiroo; Hashida, Ryuki; Takano, Yoshio; Omoto, Masayuki; Nago, Takeshi; Bekki, Masafumi; Shiba, Naoto (Journal of strength and conditioning research, 2017)
Matsuse, H, Hashida, R, Takano, Y, Omoto, M, Nago, T, Bekki, M, and Shiba, N. Walking exercise simultaneously combined with neuromuscular electrical stimulation of antagonists resistance improved muscle strength, physical function, and knee pain in symptomatic knee osteoarthritis: a single-arm study. J Strength Cond Res 31(1): 171-180, 2017-A hybrid training system (HTS) was developed as a way to combine the application of electrical stimulation and voluntary contraction. Moreover, we developed a novel training method using HTS during walking (HTSW). This study was designed to evaluate the effect of HTSW on muscle strength, physical function, and knee pain in knee osteoarthritis (KOA). Eleven subjects (age: 74.0 ± 8.5 years) participated and performed HTSW for 30 minutes 3 times a week for 12 weeks. Isokinetic knee extension/knee flexion torque, muscle volume, one-leg standing test (OST), functional reach test, 10-m maximum gait speed, timed up and go test, 6-minute walking test, knee pain using Visual Analog Scale (VAS), and Japan Knee Osteoarthritis Measure (JKOM) were assessed. Knee extension torque significantly increased from 1.02 ± 0.29 N·m·kg pretraining to 1.23 ± 0.33 N·m·kg posttraining (P < 0.01, ES = 0.68). Knee flexion torque significantly increased from 0.65 ± 0.18 N·m·kg pretraining to 0.78 ± 0.17 N·m·kg posttraining (p < 0.01). Muscle volume significantly increased from 9.00 ± 2.84 mm pretraining to 10.37 ± 3.16 mm at the end of training (p ≤ 0.05). All the physical functions except OST were significantly improved. The JKOM score improved from 26.7 ± 18.30 pretraining to 17.2 ± 14.02 at the end of training (p < 0.01). The VAS score significantly decreased from 35.4 ± 22.59 pretraining to 16.5 ± 19.73 at the end of training (p ≤ 0.05). Hybrid training system during walking may be an effective training method for the treatment of people with KOA.